Proposal of a new limited sampling strategy to predict CYP3A activity using a partial AUC of midazolam - Katzenmaier, Stephanie Katharina; Markert, Christoph; Mikus, Gerd (European journal of clinical pharmacology, 2010)
Midazolam metabolic clearance to 1′-hydroxymidazolam is an accurate measure of CYP3A activity which requires extensive plasma and urine sampling. The objective of this study was to find a new limited sampling strategy (LSS) to predict midazolam metabolic clearance to 1′-hydroxymidazolam and subsequently CYP3A activity in an easy and reliable way, reducing costs and labour.
Gesehen am 08.03.2023